An internet-of-things-based security scheme for healthcare environment for robust location privacy. (6th March 2020) - Tewari, Aakanksha; Gupta, B.B.
Recently, various applications of internet of things have been developed for the healthcare sector. Our contribution is to provide a secure and low-cost environment for the IoT devices in healthcare. The main goal is to make patients' lives easier and comfortable by providing them with more effective treatments. Nevertheless, we also intend to address the issues related to location privacy and security due to the deployment of IoT devices. We have proposed a very simple mutual authentication protocol, which provides strong location privacy by using one way hash, pseudo random number generators and bitwise operations. Strong location privacy is a key factor while ensuring healthcare security. We can enforce this property by making sure that tags in the network are indistinguishable and the protocol ensures forward secrecy. The security strength of our protocol is verified through a formal proof model for location privacy.